Bibliographical note on the syntaxonomy of the vegetation of Tlemcen, Hafir, Moutas and its reserve (North-western Algeria) (Bangladesh Journal of Plant Taxonomy, 2020)
This study provides bibliographical note on the syntaxonomy of the vegetation of Tlemcen, Hafir, Moutas of North-western Algeria, including the associations and alliances of the different higher units found in the Hafir forest and the Moutas Reserve. In this work, we observed modifications of forest and pre-forest structures according to bioclimatic variations. However, in this region, the xericity of the climate is not the only factor destroying the plant cover, anthropization is also a degradation factor. While being aware of the negative consequences, man, through their abusive cultivation, illegal logging, overgrazing, urbanization, the depletion of natural resources;, inhibits the evolution of vegetation, participates in the replacement of a rich plant cover by another and more xerophytic plant cover with thorny and/or toxic feature. The landscape is dominated, for the most part, by open and degraded formations based on therophytes and chamaephytes, linked to Rosmarinetea and Cisto-Lavanduletea. The tree structures in Hafir and the Moutas reserve, still occupy only minimal areas subject to the destructive actions of man and his flock. These formations are still linked to the Quercetea ilicis. These ecosystems are marked by a regressive evolution (forest, pre-forest, scrub, scrubland and therophytization).Bangladesh J. Plant Taxon. 27(2): 345-358, 2020 (December)